Long-term outcomes in patients with ulnar neuropathy at the elbow treated according to the presumed aetiology. Issue 8 (August 2018) - Omejec, Gregor; Podnar, Simon
Highlights: We treated patients with ulnar neuropathy at the elbow (UNE) in accordance with lesion aetiology. After 2.5 years 83% entrapments (surgery) and 84% external compressions (conservative) improved. Our results support a therapeutic approach tailored according to the presumed aetiology of the UNE. Abstract: Objectives: Ulnar neuropathy at the elbow (UNE) consists mainly of two conditions: entrapment under the humeroulnar aponeurosis (HUA) and extrinsic compression in the retrocondylar (RTC) groove. These in our opinion need different treatment: surgical HUA release and avoidance of inappropriate arm positioning, respectively. We treated our UNE patients accordingly, and studied their long-term outcomes. Methods: We invited our cohort of UNE patients to a follow-up examination consisting of history, neurological, electrodiagnostic (EDx) and ultrasonographic (US) examinations performed by four blinded investigators. Results: At a mean follow-up time of 881 days, we performed a complete evaluation in 117 of 165 (65%) patients, with 96 (90%; 35 HUA and 61 RTC) treated according to our recommendations. An improvement was reported by 83% of HUA and 84% of RTC patients. In both groups the ulnar nerve mean compound muscle action potential (CMAP) amplitude, and the minimal motor nerve conduction velocity increased, while the maximal ulnar nerve cross-sectional area (CSA) decreased. Conclusion: After 2.5 years similar proportions of HUA and RTC patients reported clinical improvement that was supported by improvement in EDx and US findings. Significance: These results suggest that patients with UNE improve following both surgical decompression and non-operative treatment. A clinical trial comparing treatment approaches in neuropathy localised to the HUA and RTC will be needed to possibly confirm our opinion that the therapeutic approach should be tailored according to the presumed aetiology of UNE.